A comparison of the conformations adopted by some 5-bromovinyl-2'-deoxyuridines and a correlation with their antiviral properties: an X-ray study. - Párkányi, L (Nucleic Acids Res, 1987)
Crystal structures of (Z)-5-(2-bromovinyl)-2'-deoxyuridine, 3',5'-di-O-acetyl-(E)-5-(2-bromovinyl)-2'-deoxyuridine and 3',5'-di-O-p-chlorobenzoyl-5-(2-dibromovinyl)-2'-deoxyuridine are compared with each other and with that of the most potent antiviral agent (E)-5-(2-bromovinyl)-2'-deoxyuridine (E-BVDU) reported earlier. A comparison of the conformation of 3',5'-di-O-acetyl-pyrimidine nucleoside structures in which intermolecular hydrogen bond network formation is minimized, with those of their parent compounds has shown that the greatest change in rotation about the glycosyl bond and in the sugar ring pucker is exhibited by E-BVDU. Upon acylation this molecule changes from C2'-endo/C3'-exo conformation to C3'-endo/C4'-exo conformation. The relevance of these structures upon the biological activity of the nucleosides and in particular to their ability to be a substrate for thymidine kinase is discussed.